2021
DOI: 10.3389/fpsyg.2021.720225
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Executive Function Skills in Preschoolers Using a Play-Based Program

Abstract: In recent years, play has been shown to be a powerful means to enhance learning and brain development. It is also known that through play children enhance their executive function (EF) skills. Furthermore, well-developed EF in preschoolers has been shown to be an important predictor for later academic and life success. Armed with this information a program, Building Brains and Futures (BBF), for developing EF through play was designed for 3–5-year-old. The program consisted of 10 simple, fun, and interactive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
8
0
2
Order By: Relevance
“…For example, digital tools and toys (Sakr & Scollan, 2019;Leung et al, 2020;Peppler et al, 2019;Li et al, 2021;Abdi & Cavus, 2019, Duncan et al, 2020Kewalramani et al, 2021;Kewalramani et al, 2020;Vogt & Hollenstein, 2021;Alemi & Haeri, 2020;Bers, 2021) even educational apps and games (Vanbecelaere et al, 2020;Adbo & Carulla, 2020;Williams & Thevenow, 2021;Ramani et al, 2020;Subaramaniam & Mon, 2020;Disney et al, 2019;Outhwaite et al, 2019). What is interesting in this data is that learning through play educational programme in many dimensions have been developed (Gibb et al, 2021;Parrott & Cohen, 2021;Theodotou, 2019). We found that very few study examined on dimension of learning through play.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, digital tools and toys (Sakr & Scollan, 2019;Leung et al, 2020;Peppler et al, 2019;Li et al, 2021;Abdi & Cavus, 2019, Duncan et al, 2020Kewalramani et al, 2021;Kewalramani et al, 2020;Vogt & Hollenstein, 2021;Alemi & Haeri, 2020;Bers, 2021) even educational apps and games (Vanbecelaere et al, 2020;Adbo & Carulla, 2020;Williams & Thevenow, 2021;Ramani et al, 2020;Subaramaniam & Mon, 2020;Disney et al, 2019;Outhwaite et al, 2019). What is interesting in this data is that learning through play educational programme in many dimensions have been developed (Gibb et al, 2021;Parrott & Cohen, 2021;Theodotou, 2019). We found that very few study examined on dimension of learning through play.…”
Section: Discussionmentioning
confidence: 87%
“…Aksoy and Baran (2020) have found differences that children who participated in play-based social skills training were detected to be at a significantly higher level in dimensions of 'communication', 'adaptation', 'selfcontrol', 'prosocial behaviours', 'assertiveness', and total social skills compared to children who have not had any intervention. More recently, Gibb et al (2021) observed improvement in all three domains of brain development, language, and motor skills. In addition, adopters of the BBF program reported that it was easily and successfully integrated into their existing preschool curricula.…”
Section: Language (12 Articles)mentioning
confidence: 96%
“…Other limitations included: (1) no professional training for those administering music interventions (e.g., parents teaching their own children songs); 20 (2) insufficient duration or training intensity (e.g., six classes, each for 20 min); 21 and (3) lack of consistency across distal measures of transfer, a limitation cited by other researchers. 22,23 Furthermore, these limitations introduce variability into potential training outcomes, lack training manuals for replication, and do not account for developmental differences in children.…”
Section: Music and Far Transfermentioning
confidence: 99%
“…Executive functions (EFs) refer to a broad range of cognitive processes responsible for the organization and deployment of cognitive resources that contribute to academic performance 1 . There is consensus that EFs include three core areas: working memory (updating), inhibition (attentional or inhibitory control), and cognitive flexibility (set‐shifting) in adults 2,3 .…”
mentioning
confidence: 99%
“…However, there is no consensus yet as to which EFs are present early and which develop later. Similarly, there is no agreement as to whether the core elements of EF are fully dissociable (Gibb et al, 2021). Therefore, teachers need to comprehend the nature of EF and develop their learning experiment management skills to design curricula, learning activities, and learning material that matches the needs of EF development.…”
Section: Introductionmentioning
confidence: 99%